Status and powering test results of HTS undulator coils at 77 K for compact FEL designs. Issue 1 (1st January 2023) - Richter, S C; Ballarino, A; Nes, T H; Schoerling, D; Bernhard, A; Müller, A-S
Abstract: The production of low emittance positron beams for future linear and circular lepton colliders, like CLIC or FCC-ee, requires high-field damping wigglers. Just as compact free-electron lasers (FELs) require high-field but as well short-period undulators to emit high energetic, coherent photons. Using high-temperature superconductors (HTS) in the form of coated ReBCO tape superconductors allows higher magnetic field amplitudes at 4 K and larger operating margins as compared to low-temperature superconductors, like Nb-Ti. This contribution discusses the development work on superconducting vertical racetrack (VR) undulator coils, wound from coated ReBCO tape superconductors. The presented VR coils were modularly designed with a period length of 13 mm. Powering tests in liquid nitrogen of multiple vertical racetrack coils were performed at CERN. The results from the measurements are presented for three VR coils and compared with electromagnetic simulations.